2001
DOI: 10.1001/archpsyc.58.4.345
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Prefrontal Cortex and Anterior Thalamus in Alcoholic Subjects on Exposure to Alcohol-Specific Cues

Abstract: When exposed to alcohol cues, alcoholic subjects have increased brain activity in the prefrontal cortex and anterior thalamus-brain regions associated with emotion regulation, attention, and appetitive behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
256
3
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(287 citation statements)
references
References 23 publications
23
256
3
4
Order By: Relevance
“…The results of this comparison were the most salient and robust effect in our original study (George et al, 2001). Confirming our earlier work, the alcoholics, and not the social drinkers, had robust activation in prefrontal and limbic regions.…”
Section: Comparison Of Alcohol Cues With Beverage Cuesmentioning
confidence: 53%
See 2 more Smart Citations
“…The results of this comparison were the most salient and robust effect in our original study (George et al, 2001). Confirming our earlier work, the alcoholics, and not the social drinkers, had robust activation in prefrontal and limbic regions.…”
Section: Comparison Of Alcohol Cues With Beverage Cuesmentioning
confidence: 53%
“…The cue-induced MRI scanning procedure was similar to our original study (George et al, 2001). Briefly, as depicted in Figure 1, alcohol and nonalcohol beverage picture cues were selected primarily from the Normative Appetitive Picture System (NAPS) (Breiner et al, 1995) but supplemented to avoid repeating the same stimuli during the scanning sequence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To establish validity of this picture set we chose a criterion that we assumed is relatively universal and uncontroversial, namely that a valid alcohol picture should elicit a greater urge to drink in heavy drinkers than in light drinkers (Drobes, 2002; George et al., 2001; Grüsser et al., 2000, 2002; Lee et al., 2006; Nees et al., 2012). In addition, we state that relative to alcohol, a valid nonalcohol picture should elicit a relatively weaker, but not a negative urge to drink in heavy drinkers compared to light drinkers.…”
mentioning
confidence: 99%
“…Many studies have indicated that passive exposure to alcohol-or drug-associated environmental cues may elicit alcohol/drug-seeking behavior in human addicts after weeks or months of abstinence (Drummond et al, 1990;George et al, 2001). In line with clinical data, ethanol is a strong reinforcer for laboratory animals (Samson et al, 2000), and alcohol-associated cues elicit drug-seeking behavior in animals trained to self-administer alcohol, even after protracted abstinence (Shalev et al, 2002;Wedzony et al, 2003;Bienkowski et al, 2004).…”
Section: Introductionmentioning
confidence: 88%